Operations planning : mixed integer optimization models - Geunes, Joseph (Operations research series., 2015)
A reference for those working at the interface of operations planning and optimization modeling, Operations Planning: Mixed Integer Optimization Models blends essential theory and powerful approaches to practical operations planning problems. It presents a set of classical optimization models with widespread application in operations planning. The discussion of each of these classical models begins with the motivation for studying the problem as well as examples of the problem's application in operations planning contexts. The book explores special structural results and properties of optimal.